2021
DOI: 10.1039/d1cy01311d
|View full text |Cite
|
Sign up to set email alerts
|

Porous organic polymer enriched in Re functional units and Lewis base sites for efficient CO2 photoreduction

Abstract: Photocatalytic reduction of CO2 into valuable chemicals or fuels is one of the promising solutions to mitigate climate changes. However, sound photocatalysts with sensitive responses to light, efficient enrichment and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…A Xe lamp (400–780 nm) was used to illuminate the solution, which was stirred at room temperature. Gas products in the system were analyzed online by a gas chromatograph (GC) every hour for a total of six times, and liquid products were qualitatively analyzed by 1 H nuclear magnetic resonance (NMR) spectra . Control experiments were conducted under similar conditions except for corresponding condition changes (Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Xe lamp (400–780 nm) was used to illuminate the solution, which was stirred at room temperature. Gas products in the system were analyzed online by a gas chromatograph (GC) every hour for a total of six times, and liquid products were qualitatively analyzed by 1 H nuclear magnetic resonance (NMR) spectra . Control experiments were conducted under similar conditions except for corresponding condition changes (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Gas products in the system were analyzed online by a gas chromatograph (GC) every hour for a total of six times, and liquid products were qualitatively analyzed by 1 H nuclear magnetic resonance (NMR) spectra. 31 Control experiments were conducted under similar conditions except for corresponding condition changes (Table S1). The PXRD patterns revealed that they are isomorphic and consistent with the patterns reported in a previous literature (Figure 1b).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The Re-bpy complex is an excellent catalytic center for the reduction of CO 2 to carbon monoxide (CO). [20][21][22][23][24][25] The triazine structure has a wide range of applications in the reaction of H 2 O oxidation to produce O 2 . [26][27][28] Moreover, the low polarity À C=CÀ can bring great carrier mobility into the obtained material.…”
Section: Introductionmentioning
confidence: 99%
“…29 To date, organic polymer-based photocatalysts have been developed for CO 2 reduction under visible light. [30][31][32][33][34][35][36][37][38][39] Metalbased catalytic sites 31,[33][34][35]39 are frequently required to selectively reduce CO 2 although some organic polymers are reported to facilitate metal-free CO 2 reduction. 30,32,[36][37][38] Hence, the design principle, that maximizes the synergy between the conjugated skeleton and catalyst moiety, is strongly desired for achieving efficient photocatalytic CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…30,32,[36][37][38] Hence, the design principle, that maximizes the synergy between the conjugated skeleton and catalyst moiety, is strongly desired for achieving efficient photocatalytic CO 2 reduction. Several combinations of the metal-based catalytic sites and organic polymers have been developed so far, 31,[33][34][35]39 while the design principles, particularly to manipulate the excited charge carrier have not been established satisfactorily. Herein, we show strong impacts of excited charge distribution in conjugated polymer photocatalysts with a site-selectively incorporated Ru(II) complex catalyst (Fig.…”
Section: Introductionmentioning
confidence: 99%